The latest trends in hair composition analysis in toxicological studies - Darmetko, Piotr; Leśków, Anna; Tarnowska, Małgorzata; Sarnowska, Marta; Wysocki, Andrzej; Pieńkowski, Marek; Szopa, Monika (Journal of Education, Health and Sport, 2018)
Humans have had to deal with toxic substances since times immemorial, and this remains the case in the present day. In case of forensic toxicology, of interest are those substances whose possession, use or effects of either imply an offense, a crime or a threat to life. Biological materials used in toxicological analyses are usually blood, urine and the vitreous body of the eye. In addition to the above-mentioned classic materials used for tests aimed at determining the presence of a given xenobiotic, alternative materials, such as hair, are increasingly being used. The primary goal of forensic and clinical toxicology is to look for a causal relationship between the presence of a toxic agent in the system and the specific biological effect caused by it. Carrying out the above objective requires the toxicology analyst to choose the appropriate diagnostic material and the appropriate analytical methods. Toxicological analysis can be performed for any type of material, including hair, which is an excellent sample for determination of individual substances. One of the most important tasks in the field of forensic toxicology is the analysis of addictive substances, whose presence or absence in the human body is one of the elements of a medico-legal report.